Analisis arah perkembangan fisik kawasan terdampak gempa di Kabupaten Sleman berbasis Nighttime Light - Arifian Dwi Wijayanto; Nur Miladan; Mochamad Primasakti Satyagraha (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Following the 2006 tectonic earthquake, Sleman Regency experienced significant spatial changes as part of the post-disaster recovery and reconstruction process. This study focuses on four subdistricts that were most severely affected, namely Berbah, Kalasan, Depok, and Prambanan. The objective of this study is to identify the direction of built-up area development in earthquake-affected regions by integrating harmonized Nighttime Light data with a spatial clockboard zoning approach. A longitudinal analysis was conducted using DMSP-OLS and VIIRS data from 2006, 2007, 2013, 2018, and 2023. The results indicate that the dominant direction of physical development shifted toward the north and northeast, moving away from high-risk zones associated with the Opak Fault. The highest light intensity was observed in ring B and the northeastern sector, suggesting a spatial growth pattern oriented toward safety and accessibility. The combined use of Nighttime Light imagery and the clockboard approach proved effective in capturing post-disaster spatial dynamics and shows potential for application in other disaster-prone regions. These findings contribute to the development of evidence-based spatial analysis methods to support adaptive and disaster-resilient regional planning.